The Change from the Creation to the Destruction of Public Value in Social and Institutional Contexts – A Case Study of CEO Peer and Policy Networks within the Dutch Social Housing Sector. (2nd November 2019) - Koolma, Hendrik Marrten; van Dreven, Catharina Frederika
Abstract : This study examines the question of which factors can explain the change from creation to destruction of public value in social and institutional environments. Second, what do CEO peer networks and policy networks in which CEOs participate contribute to such a change. The aim of the study is to design and test a comprehensive framework for understanding the change from value creation to destruction. This framework is constructed through an integration of two distinct theoretical approaches, public value management and destructive leadership. The second component is proposed, inasmuch public value management does not take into account the risk of unethical behavior of organizations' leaders. The framework is applied to a qualitative analysis of public management in the Dutch social housing sector. Interviewed CEOs of housing corporations proudly explained public value creation in the nineties. However, indications of destructive leadership outnumbered references to value creation in the first decade of this millenium. In this period, CEOs competed for dominance in peer and policy networks. Reputation drive superseded improvement drive when determining mergers and hazardous projects, unrelated to social housing purposes. Instead of authorizing, the institutional environment has been conducive to value destructing courses of action by CEOs.